Genetic Organization of the Region Encoding Regulation, Biosynthesis, and Transport of Rhizobactin 1021, a Siderophore Produced by Sinorhizobium meliloti - Lynch, Damien (American Society for Microbiology (ASM), 2001)
Eight genes have been identified that function in the regulation, biosynthesis, and transport of rhizobactin 1021, a hydroxamate siderophore produced under iron stress by Sinorhizobium meliloti. The genes were sequenced, and transposon insertion mutants were constructed for phenotypic analysis. Six of the genes, named rhbABCDEF, function in the biosynthesis of the siderophore and were shown to constitute an operon that is repressed under iron-replete conditions. Another gene in the cluster, named rhtA, encodes the outer membrane receptor protein for rhizobactin 1021. It was shown to be regulated by iron and to encode a product having 61% similarity to IutA, the outer membrane receptor for aerobactin. Transcription of both the rhbABCDEF operon and the rhtA gene was found to be positively regulated by the product of the eighth gene in the cluster, named rhrA, which has characteristics of an AraC-type transcriptional activator. The six genes in the rhbABCDEF operon have interesting gene junctions with short base overlaps existing between the genes. Similarities between the protein products of the biosynthesis genes and other proteins suggest that rhizobactin 1021 is synthesized by the formation of a novel siderophore precursor, 1,3-diaminopropane, which is then modified and attached to citrate in steps resembling those of the aerobactin biosynthetic pathway. The cluster of genes is located on the pSyma megaplasmid of S. meliloti 2011. Reverse transcription-PCR with RNA isolated from mature alfalfa nodules yielded no products for rhbF or rhtA at a time when the nifH gene was strongly expressed, indicating that siderophore biosynthesis and transport genes are not strongly expressed when nitrogenase is being formed in root nodules. Mutants having transposon insertions in the biosynthesis or transport genes induced effective nitrogen-fixing nodules on alfalfa plants.